Seed-Specific Overexpression of the Pyruvate Transporter BASS2 Increases Oil Content in Arabidopsis Seeds - Lee, Eun-Jung; Oh, Minwoo; Hwang, Jae-Ung; Li-Beisson, Yonghua; Nishida, Ikuo; Lee, Youngsook (Frontiers in Plant Science, 2017)
Seed oil is important not only for human and animal nutrition, but also for various industrial applications. Numerous genetic engineering strategies have been attempted to increase the oil content per seed, but few of these strategies have involved manipulating the transporters. Pyruvate is a major source of carbon for de novo fatty acid biosynthesis in plastids, and the embryo’s demand for pyruvate is reported to increase during active oil accumulation. In this study, we tested our hypothesis that oil biosynthesis could be boosted by increasing pyruvate flux into plastids. We expressed the known plastid-localized pyruvate transporter BILE ACID:SODIUM SYMPORTER FAMILY PROTEIN 2 (BASS2) under the control of a seed-specific soybean (Glycine max) glycinin-1 promoter in Arabidopsis thaliana. The resultant transgenic Arabidopsis plants (OEs), which expressed high levels of BASS2, produced seeds that were larger and heavier and contained 10-37% more oil than those of the wild type (WT), but were comparable to the WT seeds in terms of protein and carbohydrate contents. The total seed number did not differ significantly between the WT and OEs. Therefore, oil yield per plant was increased by 24-43% in the OE lines compared to WT. Taken together, our results demonstrate that seed-specific overexpression of the pyruvate transporter BASS2 promotes oil production in Arabidopsis seeds. Thus, manipulating the level of specific transporters is a feasible approach for increasing the seed oil content.